The Effect of The Atkyn-Karplus Model on The Acquisition And Retention of Cognitive Concepts Among Students At The Institute of Fine Arts In The Elements And Foundations of Artwork Course. (Journal of the College of Basic Education, 2025)
The current research aims to explore the impact of the Atkyn-Karplus model on the acquisition and retention of cognitive concepts among students at the Institute of Fine Arts in the Elements and Foundations of Artwork course.To verify the research objective, the researcher formulated the following null hypotheses:1. ((There are no statistically significant differences at the significance level of (0.05) between the average ranks of the scores of the experimental group students in the pre- and post-test of cognitive concepts achievement and retention.))2. ((There are no statistically significant differences at the significance level of (0.05) between the levels of ranks of the scores of the control group students in the pre- and post-test of cognitive concepts achievement and retention.))In order to verify the validity of the hypotheses, an experiment was conducted that lasted for eight weeks. The current research community consisted of first-year students of the Fine Arts Institutes in Baghdad, accredited by the General Directorates of Education, for the academic year (2024-2025), morning studies, numbering (540) students. The research sample was selected from the Fine Arts Institute/Baghdad/Al-Karkh III - Department of Fine Arts, Calligraphy and Ornamentation from first-year students/study.The morning session, which included (50) students, and the researcher adopted the experimental design with partial control with two equivalent groups with a pre-test and a post-test. After the topics of the scientific material that were taught during the experiment were determined by the experts, the teaching plans were prepared and presented to a group of experts and specialists. According to their opinions, the necessary modifications were made and the plans became ready for implementation.In order to measure its effectiveness, the researcher prepared the research tool that included the cognitive achievement test consisting of (40) multiple-choice items. To verify the validity of the test and to analyze its items, its reliability was calculated through the results of the sample students’ answers and processed statistically using statistical methods.To calculate the statistical indicators for the achievement test and reach the application results later, the researcher is required to use the statistical package (SPSS) to extract those statistical indicators.The most important results reached by the research are the presence of statistically significant differences at a significance level of (0.05) between the average ranks of the scores of the students of the experimental group in the pre- and post-achievement test. Therefore, the effect size of the Atkin-Karplus model on cognitive achievement has a large and high effect on the students of the experimental group